Morphological manifestations of experimental paclitaxel-induced sciatic neuropathy under correction of 2-ethyl-6-methyl-3-hydroxypyridine succinate - Ostrovskyi, Mykola (ScienceRise: Medical Science, 2021)
Paclitaxel is an effective chemotherapeutic agent for many cancers, but it has a number of limiting side effects that not only significantly reduce the quality of life of patients, but also limit their further treatment. Peripheral neuropathy is one of these, but there are currently no proven effective druHS for the prevention or treatment of paclitaxel-induced neuropathic pain (PINP) in particular, or chemotherapy-induced peripheral neuropathy (CIPN) in general. 2-ethyl-6-methyl-3-hydroxypyridine succinate (HS) is a derivative of succinic acid with neuroprotective, antihypoxic, membrane-protective, nootropic, sedative effects. The aim of the study was to study the effect of the neuroprotective agent HS on the pathomorphogenesis of the sciatic nerves under conditions of paclitaxel-induced peripheral neuropathy in the experiment. Materials and methods. The experiment was carried out on 80 white rats, which were injected intraperitoneally with paclitaxel (Actavis, Romania), previously dissolved in isotonic saline at a dose of 2 mg / kg of body weight four times every other day until a total dose of 8 mg / kg was reached. Then forty of these animals were injected intraperitoneally with 2-ethyl-6-methyl-3-hydroxypyridine succinate at a dose of 10 mg / kg (the remaining 40 rats received intraperitoneal water for injection). Morphological studies were carried out on the first, seventh, fifteenth, twenty-eighth, sixtieth, ninetieth and one hundred and twentieth days after the last injection of the drug. We investigated the pharmacological potential of HS in the prevention and treatment of CIPN at the level of sciatic nerve (SN) morphology. Results. The maximum value of the average profile area of myelinated nerve fibers with the use of HS is significantly lower than with uncorrected flow, and is (78.12±2.24) μm2 compared to (94.04±1.03) μm2 (p <0.001). The introduction of HS provides a stable content of the value of the ratio of the areas of the axial cylinder and the fiber within 0.39±0.01 (first day) - 0.44±0.01 (ninetieth day), and a rapid recovery of the indicator value to normal values during the final 30 days of the experiment. the maximum value of the index of the profile area of the myelin sheath with the introduction of HS is 1.4 times less than with an uncorrected flow, and is, respectively, (49.01±1.59) μm2 and (69.77±1.87) μm2 (p <0.001). HS provides a more intensive restoration of the indicator of the area of the myelin sheath during the 90th - 120th day of the experiment. Conclusions. Our results allow us to conclude that the introduction of HS creates a protective effect against paclitaxel-induced peripheral neuropathy (PIPN) by acting on both the axial cylinder and the myelin sheath of the heart failure. Due to the known pathophysiological mechanisms of the development of neuropathy, this method can be a promising therapeutic agent for the prevention and treatment of PIPN